Media law for journalists - Smartt, Ursula (Abongdon, Oxon ; New York, NY : Routledge, 2021)
This book is both an introductory text and reference guide to the main issues facing journalists today, including social media, fake news, and regulators. The text covers the law of the United Kingdom - including Scots and Northern Irish devolved legislation - as well as human rights and EU laws. This book covers essential areas such as: privacy, confidentiality, freedom of expression and media freedom, defamation, contempt of court, regulation of the print press and broadcast regulation as well as discussions on fake news and how to regulate online harm. There is a section on intellectual property law, covering mainly copyright. Court reporting and how to report on children, young people and victims of sexual offences receive particular attention in this book with relevant cases in user-friendly format. The engaging writing style is aimed to enthuse students, practitioners and lecturers with plenty of examination and practice materials. The text is packed with extensive learning aids including case studies, boxed notes, sample examination questions, appendices of statutes and cases and a glossary. It is intended as a complete course textbook for students and teachers of journalism, media, communications and PR courses, focusing on diploma courses, NCTJ examinations and broadcast journalism courses such as the BJTC. The book's international focus would also make it ideal reading for journalists from across the world who are working in the UK. The book presumes no prior legal knowledge.
1. The legal systems in England and Wales, Scotland and Northern Ireland; 2. Human rights: privacy and media freedom; 3. Defamation; 4. Court reporting; 5. Contempt of Court; 6. Freedom of information and data protection; 7. Social media and fake news; 8. Regulators; 9. Intellectual property law.
Previous edition: London: SAGE, 2006.
OCLC-licensed vendor bibliographic record.
Keywords: Press law -- Great Britain; Journalists -- Legal status, laws, etc. -- Great Britain; LAW / General